Case report of idiopathic scapular dyskinesia: Revisiting involuntary scapular movements from a neurologist’s perspective - Anjali Chouksey; Ganeshgouda Majigoudra (Annals of Movement Disorders)
Scapular dyskinesia, one of the rare forms of focal dyskinesia, is usually considered a peripheral induced movement disorder (PIMD), occurring in the background of previous trauma or surgery. Different terms are used interchangeably with scapular dyskinesia, many of which are misleading. In this article, we present 2 cases of patients with abnormal involuntary scapular movement suggestive of scapular dyskinesia. In both cases, there is no history of preceding trauma or surgical intervention. We will review the literature and try to understand the fundamental difference between the various terms used for abnormal scapular movement in literature. Our cases highlight the difference between the two commonly used terms for scapular movement, i.e., scapular dyskinesia and scapular dyskinesis. We further suggest that shoulder girdle dyskinesia should be preferred over scapular dyskinesia. Although scapular dyskinesia is often considered PIMD, not all cases of scapular dyskinesia are peripherally induced.